Pengaruh Metode Socrates terhadap Kemampuan Penalaran dalam Membuktikan Teorema Limit pada Perkuliahan Analisis Real I - Molli Wahyuni; Astuti; Yuslenita Muda; I Made Arnawa (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2025)
Reasoning ability is an essential foundation for someone in proving a theorem, especially in proving abstract limit theorems in Real Analysis I. Sometimes, students only record the theorem narrative without paying attention to the flow of reasoning up to the final argument. Therefore, a learning model that can explore and train the reasoning process is needed. This study aims to analyze the effect of the Socratic Method on students' reasoning ability in proving limit theorems in the Real Analysis I course. This study used a One-Group Pretest-Posttest Design. The research subjects were 14 fifth-semester students of the Mathematics Education Study Program, Pahlawan Tuanku Tambusai University. The instrument used was a reasoning ability test in proof consisting of 3 essay questions, with questions on limit theorems (sequence limit and function limit) that had been validated. The treatment given was learning using the Socratic Method for 4 meetings. The data obtained were analyzed using the paired sample t-test with a significance level α = 0.05. The results showed that the average pretest score (42.14) and posttest score (77.86) had a significant mean difference. From the paired t-test, the t-value (12.45) > t-table (2.160) with p-value 0.000 < 0.05. The Socratic Method influences students' reasoning ability in proving limit theorems. The method effectively trains students in forming logical arguments, connecting concepts, and understanding the essence of formal proof.